SELECTION OF LINEAR DEMAND FUNCTION PARAMETERS FOR ENSURING THE CORRECT SUBSTITUTION EFFECT CALCULATION - Popov, В.В. (Journal of Information Technologies in Education (ITE), 2014)
In the course of microeconomics it is convenient to use additive functions of requirements in educational purposes, in which the volume of requirements is set by the linear function of the price,revenue and other factors. But in arriving at the substitution effect there is a number of problems in which impossible answers come out. The formula adjustment concluded by the author, which will allow to avoid contradictions, is described in the article